2019
DOI: 10.3390/genes10100772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Epidemiology and Clinical Features of Hereditary Hearing Impairment in the Taiwanese Population

Abstract: Hereditary hearing impairment (HHI) is a common but heterogeneous clinical entity caused by mutations in a plethora of deafness genes. Research over the past few decades has shown that the genetic epidemiology of HHI varies significantly across populations. In this study, we used different genetic examination strategies to address the genetic causes of HHI in a large Taiwanese cohort composed of >5000 hearing-impaired families. We also analyzed the clinical features associated with specific genetic mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 94 publications
5
29
0
Order By: Relevance
“…The presence of OAE is main reason for missing OTOF-related ANSD at NBHS. Similar to our result, it was reported that 75% of OTOF-related patients improperly passed NBHS in a previous study (Wu et al 2019). The risk of using OAE for NBHS has been discussed from the point of view of its inability in detecting ANSD.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of OAE is main reason for missing OTOF-related ANSD at NBHS. Similar to our result, it was reported that 75% of OTOF-related patients improperly passed NBHS in a previous study (Wu et al 2019). The risk of using OAE for NBHS has been discussed from the point of view of its inability in detecting ANSD.…”
Section: Discussionsupporting
confidence: 93%
“…Patient 27 is of Italian origin and patient 29 has French origins, thus suggesting that TMPRSS3 mutations might be more frequently involved in non-syndromic HL than reported in the literature, even in Caucasian patients [11,45,69]. As shown previously, the local epidemiology and diagnostic rate vary widely regarding ethnicity [11,[70][71][72]. Geneva is a city located at the crossroads of Europe and is known for its mixed ethnicity and thus our rates probably do not reflect a classical Western Europe Caucasian population epidemiology.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, we reported a third cluster of familial TSAN, which includes three cases with two variants of the OTOF gene (which encodes otoferlin protein), c.5098G > C (p.Glu1700Gln) and c.4882C > A (p.Pro1628Thr). The reasons why both variants were considered part of the cause of TSAN in this family are as follows: (1) both are missense variants affecting residues that are completely preserved among different species; (2) p.Glu1700Gln has been shown to be pathogenic (Chiu et al, 2010;Chen et al, 2018;Qiu et al, 2019;Wu et al, 2019); (3) p.Pro1628Thr, which is reported here for the first time, was absent in 200 normal controls and has a very low allele frequency in a public database (8.67 × 10 −6 in ExAC); and (4) both variants strongly co-segregated with the TSAN phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the three cases (with the identical twin brothers regarded as representing one case) involving subjects who were TSAN patients, the subjects were compound heterozygotes for the two variants, and both parents were unaffected and heterozygous (Figure 1). The c.5098G > C variant, which occurred in exon 40 and was inherited from the unaffected mother (I-2), resulted in a glutamic acid-to-glutamine substitution at position 1,700 and has been previously reported as a pathogenic allele (Chiu et al, 2010;Chen et al, 2018;Qiu et al, 2019;Wu et al, 2019). The other variant, c.4882C > A, which was located in exon 39 and passed on from the clinically normal father (I-1), resulted in a single amino acid change from a proline to a threonine at position 1,628 in otoferlin.…”
Section: Variant Validation and Analysismentioning
confidence: 99%